The Science Around Me: Creating Pre-Service Teachers' Portfolio Focused on Developing Scientific Questions and Explaining Relevance - Roemmele, Christopher (Innovations in Science Teacher Education, 2025)
Pre-service teachers (PSTs) in elementary and middle grades teacher preparation programs may not feel comfortable with teaching science content and developing science lessons. To encourage and support elementary and middle grades pre-service teachers (PSTs) growth, interest, and confidence in teaching science, I created a portfolio assignment called The Science Around Me that focused on the PSTs’ developing scientific questions and explaining phenomena relevance. PSTs utilized photographs and videos from their own lives and experiences. The portfolio documents PSTs ability to develop scientific questions (in the manner of Cruz-Guzman, 2017) that could potentially lead to sensemaking investigations using the Science and Engineering Practices (SEPs) and explain the relevance of scientific phenomena to their future students at three different levels. The scope of tasks increased each week as students were given constant formative guidance and feedback. Student feedback was generally positive and helped their ability to “see” the science in their own lives, generate questions about it, and explain its relevance. If PSTs can develop these pedagogical skills, this ability can be transferred to their future students to recognize the science around them in their lives.